Clinical profile in cases of intestinal perforation - Utaal, Maneshwar Singh; Bali, Sharadendu; Batra, Pooja; Garg, Navdeep (International Surgery Journal, 2017)
Background: Intestinal perforation is a surgical emergency with a wide variety of clinical features and causes. Regional variations are common with regards to the cause of intestinal perforation, and need to be evaluated in local settings. The study was conducted to determine the clinical profile of patients with intestinal perforation, with regard to clinical presentation, investigative results, pathological features, surgical findings, complications and outcome. Methods: Detailed information was recorded on 40 cases of intestinal perforation with regard to clinical features, investigative results, surgical findings, post-operative course and outcome. The data was analysed with appropriate statistical methods. Results: The site of perforation was gastric 27.5%, duodenum 20%, jejunum 5%, ileum 35%, appendix 10% and colon 2.5%. Main causes included peptic ulcer 42.5%, typhoid 25% and few cases of trauma, tuberculosis, appendicitis and malignancy. Peritonitis was universal. Primary repair, resection with anastomosis, appendectomy and stoma were the operative procedures. Morbidity rate was 60.0% and mortality rate was 12.5%. Conclusions: Commonest site of perforation was gastro-duodenal while commonest cause was peptic ulcer disease. Morbidity and mortality was comparable with other studies.